An unusual variant of ascites: congenital chylous ascites - Jeena, Sumit; Londhe, Atul C.; Joshi, Amol; Deshmukh, L. S.; Patil, Hemant N. (International Journal of Contemporary Pediatrics, 2025)
Chylous ascites is a rare condition. It is defined as the accumulation of chyle into the peritoneal cavity in infants younger than three months. Most common cause of its occurrence is malformation of the intra-abdominal lymphatic system. Other pathological conditions like malignant neoplasms, infections, liver cirrhosis, blunt abdominal trauma and surgery injury (iatrogenic injury) can also result in chylous ascites. The objective of this case report is to describe the case of a neonate with chylous ascites, establishing its diagnosis and the proposed medical treatment. A late preterm, female neonate born at 36 weeks of gestation with moderate abdominal distension was admitted in NICU and managed conservatively. At day 2 of life, diagnostic and therapeutic ascitic fluid tapping was done. Initial evaluation revealed normal blood and ascitic fluid investigations. Triglycerides were also normal (40 gm/dl) and done for exclusion of diagnosis of chylous ascites. Ascites was of exudative in nature, straw coloured with no malignant cells. At day 12 of life, in abdominal paracentesis ascitic fluid was cloudy in appearance with high triglycerides (1342 mg/dl), diagnostic of chylous ascites. Neonate was managed with withholding breastfeeding, medium chain triglyceride based rich diet, high protein diet, injection octreotide along with abdominal girth monitoring and close follow-up. Neonatal ascites improved gradually during 2 months of medical treatment following which breast feeding was introduced since long chain fatty acids are important for optimal brain growth in neonates and the baby started gaining weight.